Beyond Exceptionalism Traces of Slavery and the Slave Trade in Early Modern Germany, 1650-1850 - Mallinckrodt, Rebekka; Köstlbauer, Josef; Lentz, Sarah (De Gruyter, 2021)
While the economic involvement of early modern Germany in slavery and the slave trade is increasingly receiving attention, the direct participation of Germans in human trafficking remains a blind spot in historiography. This edited volume focuses on practices of enslavement taking place within German territories in the early modern period as well as on the people of African, Asian, and Native American descent caught up in them.